Resin composition, resin molding and method for producing resin composition
A resin composition with thermoplastic resin and glycol-modified lignin addresses the limitations of polycarbonate resin molded bodies by enhancing printability, coatability, and adhesion, while maintaining mechanical properties and durability.
Patent Information
- Application Number
- JP2023094114
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
AI Technical Summary
Existing polycarbonate resin molded bodies lack printability, coatability, and adhesion, despite their mechanical properties and durability.
A resin composition containing a thermoplastic resin and modified lignin, which is modified with glycols, is developed to enhance printability, coatability, and adhesion, with specific surface energy and contact angle ranges to ensure compatibility and processability.
The resin composition achieves excellent mechanical properties, durability, and adhesion while improving printability and coatability, utilizing biomass raw materials effectively.
Smart Images

Figure 2024175965000005 
Figure 2024175965000006 
Figure 2024175965000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin molded article having functionality, and a method for producing the resin composition. [Background technology]
[0002] Lignin is a natural biomass that constitutes plants along with cellulose and hemicellulose. Wood contains approximately 20-35% by mass of lignin. Many herbaceous plants also contain lignin. Lignin improves the physical strength of plant cell walls, prevents decomposition by living organisms, and controls water fluidity by imparting hydrophobicity to the cell walls. The basic structure of lignin is parahydroxyphenylpropane. Lignin is an irregular polymer produced by dehydrogenation polymerization of p-coumaryl alcohol, coniphenyl alcohol, and sinapyl alcohol, each of which has 0-2 methoxyl groups.
[0003] In recent years, attempts to utilize lignin have been investigated for the purpose of effective utilization of biomass raw materials (see, for example, Patent Documents 1 and 2). Patent Document 3 describes that by using lignophenol as a substitute for petroleum materials in resin molded products, it is possible to obtain polycarbonate resin molded products that are environmentally friendly, have high impact resistance, excellent heat resistance and flame retardancy, and also have a good molded appearance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2021-123717 A [Patent Document 2] International Publication No. 2021 / 015190 [Patent Document 3] Patent No. 5787354 Summary of the Invention [Problem to be solved by the invention]
[0005] Although Patent Document 3 describes that the polycarbonate resin molded body has mechanical properties and durability, it does not describe the printability, coatability, or adhesion of the polycarbonate resin molded body.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a resin composition for a resin molded body that effectively utilizes biomass raw materials and has excellent mechanical properties and durability as well as printability, coatability, and adhesion compared to general-purpose resins, a resin molded body obtained by molding the resin composition, and a method for producing the resin composition. [Means for solving the problem]
[0007] As a result of intensive research, the present inventors have discovered that a resin composition having excellent processability, which contains modified lignin, a biomass raw material, and a general-purpose thermoplastic resin, can be used to impart not only mechanical properties and durability, but also printability, coatability, and adhesion to a resin molded article, and have thus completed the present invention.
[0008] That is, the present invention has the following aspects. [1] A resin composition comprising a thermoplastic resin and a modified lignin modified with glycols. [2] The surface free energy of a resin molded body made of the thermoplastic resin and the modified lignin is 30 mJ / m 2 More than 100mJ / m 2 The resin composition according to [1], [3] The resin composition according to [1] or [2], wherein the SP value of the monomer constituting the thermoplastic resin is 10 or more and 40 or less. [4] A resin molding made of the thermoplastic resin and the modified lignin has a contact angle with water of 30° or more and 120° or less; The surface free energy of a resin molded body made of the thermoplastic resin and the modified lignin is 40 mJ / m 2 More than 90mJ / m 2 The resin composition according to any one of [1] to [3] below. [5] The resin composition according to any one of [1] to [4], wherein the thermoplastic resin has a melt viscosity at 230°C and 100 rad / s of 10 Pa·s or more and 10,000 Pa·s or less. [6] The resin composition according to any one of [1] to [5], wherein the modified lignin has a mass average molecular weight of 100 or more and 50,000 or less. [7] The contact angle of the coating film made of the modified lignin with water is 30° or more and 100° or less; The surface free energy of the coating film made from the modified lignin is 40 mJ / m 2 More than 120mJ / m 2 The resin composition according to any one of [1] to [6] below. [8] The resin composition according to any one of [1] to [7], wherein the modified lignin has a melt viscosity at 230°C and 100 rad / s of 10 Pa·s or more and 50,000 Pa·s or less. [9] The resin composition according to any one of [1] to [8], wherein the glycols include at least one selected from the group consisting of polyethylene glycol, methoxypolyethylene glycol, polypropylene glycol, polybutylene glycol, and polyoxyalkylene bisphenol.
[10] The resin composition according to any one of [1] to [9], further comprising a compatibilizer.
[11] A resin molded product comprising the resin composition according to any one of [1] to
[10] .
[12] A method for producing the resin composition according to any one of [1] to
[10] , A method for producing a resin composition, comprising a step of kneading a thermoplastic resin and a modified lignin modified with glycols to obtain a resin composition. Effect of the Invention
[0009] According to the resin composition of the present invention, a resin composition having good processability can be obtained by effectively utilizing a biomass raw material. By using the resin composition of the present invention, a resin molded product having excellent mechanical properties and durability, as well as excellent coatability, printability, and adhesion can be obtained. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view that illustrates a resin molded body according to an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view illustrating a laminated film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] ≪Resin composition≫ A resin composition according to one embodiment of the present invention contains a thermoplastic resin and modified lignin modified with glycols.
[0012] <Thermoplastic resin> A thermoplastic resin is a resin that is softened by heating and can be molded by heating. A thermoplastic resin is a resin whose glass transition point or melting point is at least 25°C or higher and 400°C or lower.
[0013] The SP value of the monomer constituting the thermoplastic resin is preferably 10 to 40, more preferably 20 to 30. When the SP value is equal to or greater than the lower limit, the compatibility with the modified lignin is good, and a resin molded product having excellent mechanical properties, printability, coatability, and adhesion can be obtained. When the SP value is equal to or less than the upper limit, a resin molded product having excellent water resistance can be obtained. The SP value can be calculated from the molecular structure using the Hansen Solubility Parameter software HSPiP (Hansen Solubility Parameter in Practice). When the chemical structure is entered in Smile notation on the input screen of the software, it is divided into atomic groups using a neutral network called the Yamamoto Molecular Break (Y-MB) method, and the HSP value can be calculated, and the total value of the dispersion term, polar term, and hydrogen bond term can be obtained as the SP value. For thermoplastic resins composed of multiple monomers in a specified ratio, the SP value is calculated using the oligomer, which is the smallest unit.
[0014] The contact angle of water of a resin molded product made of a thermoplastic resin and modified lignin is preferably 30° or more and 120° or less, more preferably 50° or more and 110° or less, and even more preferably 80° or more and 100° or less. When the contact angle is equal to or more than the lower limit, the water resistance of the resulting resin molded product is good. When the contact angle is equal to or less than the upper limit, the modified lignin becomes easily dispersible and compatible, and the mechanical properties, coatability, printability, and adhesion of the resulting resin molded product are also good. The contact angle of a thermoplastic resin with water can be measured using a resin molded body obtained by molding thermoplastic resin pellets by hot pressing, etc. The contact angle of a thermoplastic resin with water can be measured, for example, by dropping a water droplet with a liquid volume of 1.5 μL onto a thermoplastic resin sheet at 25° C. using a contact angle meter (Portable Contact Angle Meter PCA-1, manufactured by Kyowa Interface Science Co., Ltd.) and evaluating the contact angle of the droplet after 1 second.
[0015] The surface free energy of the resin molded body made of thermoplastic resin and modified lignin is 30 mJ / m 2 More than 100mJ / m 2 It is preferable that the concentration is less than 40 mJ / m 2 More than 90mJ / m 2 or less, and more preferably 60 mJ / m 2 More than 80mJ / m 2 When the surface free energy is equal to or greater than the lower limit, the compatibility with modified lignin is good, the mechanical properties and wettability of the resulting resin molded article are good, the occurrence of bleeding and cissing can be suppressed, and the printability and adhesion are excellent. When the surface free energy is equal to or less than the upper limit, the water resistance of the resulting resin molded article is good. The surface free energy can be calculated by applying the Kitazaki-Hata theory to the contact angles measured with three types of solvents for a resin molded body made from a thermoplastic resin in the measurement of the contact angle with water. The three types of solvents that can be used are water (distilled water), diiodomethane, and hexadecane. The value of the surface free energy can be calculated based on the arithmetic average value of the contact angles measured 10 times at different measurement points.
[0016] The melt viscosity of the thermoplastic resin at 230°C and 100 rad / s is preferably 10 Pa·s or more and 10,000 Pa·s or less, more preferably 50 Pa·s or more and 8,000 Pa·s or less, and even more preferably 100 Pa·s or more and 5,000 Pa·s or less. When the melt viscosity of the thermoplastic resin is equal to or more than the lower limit, tension is maintained during processing such as melt kneading, and pellet production becomes easy. When the melt viscosity of the thermoplastic resin is equal to or less than the upper limit, the flowability of the molten resin becomes good, it becomes easy to mix with the modified lignin, and the processability becomes good. The melt viscosity of a thermoplastic resin can be measured using a rheometer. The melt viscosity at 100 rad / s can be measured by using parallel plates with a diameter of 25 mm in a nitrogen atmosphere at a temperature equal to or higher than at least one of the softening point and melting point of the thermoplastic resin and at frequencies from 100 rad / s to 1 rad / s.
[0017] Examples of thermoplastic resins include olefin resins, polyester resins, polyamide resins, vinyl resins, acrylic resins, cellophane, alkyd resins, polyester resins, polyether resins, polyamine resins, phenol resins, melamine resins, epoxy resins, and engineering plastics. Examples of olefin resins include polyethylene, polypropylene, polymers of olefins having 2 to 10 carbon atoms, and propylene-ethylene copolymers. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate.
[0018] Examples of polyamide resins include aliphatic polyamides such as nylon 6 and nylon 66, and aromatic polyamides such as polymetaxylylene adipamide. Examples of vinyl resins include polystyrene, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer. Examples of the acrylic resin include homopolymers or copolymers of (meth)acrylic monomers such as polymethyl methacrylate, polyacrylonitrile, and ethylene methacrylic acid copolymers. The (meth)acrylic monomer refers to at least one of an acrylic acid monomer and a methacrylic acid monomer.
[0019] The urethane resin is a resin having a urethane bond formed by a polyol and an isocyanate compound. Examples of the polyols contained in the urethane resin include at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol. The acrylic polyol may be obtained by polymerizing an acrylic acid derivative monomer, or may be obtained by copolymerizing an acrylic acid derivative monomer with another monomer. Examples of the acrylic acid derivative monomer include ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate. Examples of the monomer to be copolymerized with the acrylic acid derivative monomer include styrene.
[0020] Examples of the isocyanate compound include aromatic tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), aliphatic hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), and other monomers, polymers thereof, and derivatives thereof. The above-mentioned isocyanate compounds may be used alone or in combination of two or more. Examples of engineering plastics include polycarbonate and polyimide.
[0021] Among the above thermoplastic resins, polyamide-based resins, acrylic-based resins, and urethane-based resins are preferred from the viewpoint of compatibility with modified lignin. These resins may be used alone or in combination of two or more.
[0022] The content of the thermoplastic resin relative to the total mass (100% by mass) of the resin composition is preferably 10% by mass or more and 97% by mass or less, more preferably 20% by mass or more and 90% by mass or less, and even more preferably 30% by mass or more and 80% by mass or less. When the content of the thermoplastic resin is equal to or more than the lower limit, the flowability and processability during melt kneading are good. When the content of the thermoplastic resin is equal to or less than the upper limit, the degree of biomassification can be increased, and the function derived from the modified lignin is exerted, and a resin molded product having good durability, mechanical properties, coatability, printability, and adhesion can be obtained.
[0023] <Modified lignin> Lignin is a natural biomass that constitutes plants along with cellulose and hemicellulose. Lignin is a polymer compound whose basic structure is parahydroxyphenylpropane. Since lignin has a very complex molecular structure, it is difficult to uniformly specify its chemical structure by a general formula or the like. The resin composition of the present embodiment contains modified lignin, and thus can effectively utilize biomass raw materials. In the resin composition of the present embodiment, the modified lignin is a lignin derived from a plant and modified with a glycol. The modified lignin may be a lignin modified with a glycol, and the detailed structure, preparation method, etc. are not particularly limited.
[0024] The mass average molecular weight of the modified lignin is, for example, preferably 100 to 50,000, more preferably 1,000 to 30,000, and even more preferably 5,000 to 20,000. When the mass average molecular weight of the modified lignin is equal to or greater than the lower limit, the scratch resistance of the resulting resin molded product is good. When the mass average molecular weight of the modified lignin is equal to or less than the upper limit, the adhesion of the resulting resin molded product to printing ink or the like is improved, and the ease of printing (printability) on the resin molded product is further improved. The mass average molecular weight of the modified lignin can be measured, for example, by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0025] The melt viscosity of the modified lignin at 230°C and 100 rad / s is preferably 10 Pa·s or more and 50,000 Pa·s or less, more preferably 50 Pa·s or more and 30,000 Pa·s or less, and even more preferably 100 Pa·s or more and 20,000 Pa·s or less. When the melt viscosity of the modified lignin is equal to or more than the lower limit, tension is maintained during processing such as melt kneading, and the moldability of the resin molded body is good. When the melt viscosity of the modified lignin is equal to or less than the upper limit, the fluidity of the molten resin is good, kneading is easy, and it is easy to mix with a thermoplastic resin. The melt viscosity of the modified lignin can be measured using a rheometer. The melt viscosity at 100 rad / s can be measured by using parallel plates with a diameter of 25 mm under a nitrogen atmosphere at a temperature equal to or higher than at least one of the softening point and melting point of the modified lignin at frequencies from 100 rad / s to 1 rad / s.
[0026] The contact angle of the coating film made of the modified lignin to water is preferably 30° to 100°, more preferably 50° to 90°, and even more preferably 60° to 80°. When the contact angle is equal to or greater than the lower limit, a resin molded product having excellent compatibility with thermoplastic resins, excellent water resistance, and mechanical properties can be obtained. When the contact angle is equal to or less than the upper limit, a resin molded product having excellent processability, flowability, good wettability, printability, and adhesion can be obtained. The contact angle of modified lignin with water can be measured by dissolving the modified lignin in a solvent such as tetrahydrofuran (THF), coating it on a plastic substrate such as polyethylene terephthalate (PET), and drying it to create a coating film with a thickness of approximately 2 μm.A 1.5 μL droplet of water is then dropped onto the coated film at 25°C using a contact angle meter (Kyowa Interface Science Co., Ltd., Portable Contact Angle Meter PCA-1) and the contact angle of the droplet after 1 second is evaluated.
[0027] The surface free energy of the coating made from modified lignin is 40 mJ / m 2 More than 120mJ / m 2It is preferable that the concentration is less than 50 mJ / m 2 More than 100mJ / m 2 or less, and more preferably 60 mJ / m 2 More than 80mJ / m 2 When the surface free energy is equal to or greater than the lower limit, the wettability, printability, and adhesion are good. When the surface free energy is equal to or less than the upper limit, the compatibility with the resin is good, and the resin molded product 1 having excellent mechanical properties and water resistance can be obtained. The surface free energy can be calculated by measuring the contact angle of modified lignin with water, by preparing a coating of modified lignin, measuring the contact angle in three different solvents, and applying the Kitazaki-Hata theory. The three solvents that can be used are water (distilled water), diiodomethane, and hexadecane. The value of the surface free energy can be calculated based on the arithmetic average value of the contact angle measured 10 times at different measurement points.
[0028] Examples of lignin derived from plants that is used as a raw material for the modified lignin in this embodiment include lignin derived from woody plants and lignin derived from herbaceous plants. Examples of lignin derived from woody plants include coniferous lignin contained in coniferous trees, and broad-leaved lignin contained in broad-leaved trees. Examples of coniferous trees include spruce, red pine, cedar, and cypress. Examples of broad-leaved trees include birch and beech. Examples of lignin derived from herbaceous plants include rice lignin contained in plants of the family Gramineae. Examples of grasses include wheat straw, rice straw, corn, bamboo, and reeds. Although not particularly limited, in view of the stability of the material, it is preferable to use lignin derived from a woody plant, it is more preferable to use coniferous lignin, and it is even more preferable to use cedar lignin. As the lignin, these materials may be used alone or in combination of two or more.
[0029] The glycols constituting the modified lignin in this embodiment are a type of alcohol, and are compounds having a structure in which hydrogen atoms bonded to two carbon atoms of an aliphatic hydrocarbon having two or more carbon atoms or a cyclic aliphatic hydrocarbon are replaced with hydroxyl groups. Examples of glycols include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, methoxypolyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, polybutylene glycol, glycerin, hexylglycerin, ethylhexylglycerin, polyglycerin, pentylene glycol, 1,2-hexanediol, caprylyl glycol, and polyoxyalkylene bisphenol. These glycols may be used alone or in combination of two or more.
[0030] The mass average molecular weight of the glycols is preferably 50 or more and 10,000 or less, more preferably 200 or more and 2,000 or less, and even more preferably 400 or more and 800 or less, from the viewpoints of compatibility with thermoplastic resins and processability. The mass average molecular weight of the glycols can be measured, for example, by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0031] The content of the glycol-based units is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 100 parts by mass or less, and even more preferably 50 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the modified lignin. When the content of the glycol-based units is equal to or more than the lower limit, the flowability and processability during melt kneading are good, and a resin molded product having good coatability and printability is obtained. When the content of the glycol-based units is equal to or less than the upper limit, the biomass content of the resin molded product can be increased, and the durability, mechanical properties, and adhesion are good.
[0032] The content of the modified lignin-based unit in the resin composition is, for example, preferably 3% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 80% by mass or less, and even more preferably 20% by mass or more and 70% by mass or less, based on the total mass (100% by mass) of the resin composition. When the content of the modified lignin-based unit is equal to or more than the lower limit, the degree of biomass conversion can be increased, and the function derived from the modified lignin can be exerted, resulting in a resin molded product having good durability, mechanical properties, coatability, printability, and adhesion. When the content of the modified lignin-based unit is equal to or less than the upper limit, the flowability and processability during melt kneading are good.
[0033] The method for producing the modified lignin is not particularly limited. For example, the modified lignin can be obtained by digesting a plant material, which is the raw material for the lignin, with glycols. The digestion method is not particularly limited, but for example, a plant material that is the raw material for lignin, glycols, and an inorganic acid (for example, hydrochloric acid, sulfuric acid, etc.) as an acid catalyst are mixed and reacted. The mixing ratio of the glycols per 100 parts by mass of the plant material that is the raw material for lignin is, for example, 200 parts by mass or more, preferably 300 parts by mass or more, and for example, 1,000 parts by mass or less, preferably 600 parts by mass or less.
[0034] The mixing ratio of the inorganic acid (100% conversion) per 100 parts by mass of the glycols is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, and for example, 2 parts by mass or less, preferably 1 part by mass or less.
[0035] The reaction conditions are as follows: under normal pressure, the reaction temperature is, for example, 120° C. or more, preferably 130° C. or more, and for example, 180° C. or less, preferably 150° C. or less. The reaction time is, for example, 60 minutes or more and, for example, 240 minutes or less, preferably 120 minutes or less.
[0036] After the reaction is completed, a known alkali (e.g., ammonia, sodium hydroxide, etc.) is added in an appropriate ratio to adjust the pH and extract the modified lignin into the solution. The adjusted pH is, for example, 8 or more, preferably 10 or more, more preferably 10.5 or more, and for example, 14 or less. By such a method, pulp is obtained as a solid component, and modified lignin is obtained as a solution component (pulp waste liquor).
[0037] Next, the solid component (pulp) is separated from the reaction product by a known separation method such as filtration, pressing, centrifugation, etc., and the solution component (pulp waste liquid) is recovered. If necessary, the solid component (pulp) can be washed, and the solution (modified lignin) impregnated in the solid component can be recovered.
[0038] Thereafter, an inorganic acid (e.g., hydrochloric acid, sulfuric acid, etc.) is added to adjust the pH to precipitate and deposit the modified lignin. The adjusted pH is, for example, 1.5 or more and, for example, 5 or less, preferably 3 or less, and more preferably 2 or less. This allows the modified lignin to precipitate. The resulting precipitate can be collected by a known method such as filtration, pressing, or centrifugation to obtain the modified lignin as a solid content.
[0039] <Compatibilizer> The resin composition preferably contains a compatibilizer. The compatibilizer may be non-reactive or reactive. Examples of non-reactive compatibilizers include hydrogenated styrene butadiene rubber (SBR), styrene-ethylene-butylene-styrene block copolymer (SEBS), polystyrene-polyisoprene-polystyrene triblock copolymer (SIPS), and polystyrene (PS) and acrylonitrile-styrene copolymer (AS) graft polymers such as PE-g-PS, PE-g-PS, PE-g-AS, PP-g-AS, and EEA-g-AS.
[0040] Reactive compatibilizers are resins that are compatible with thermoplastic resins and react with the functional groups of modified lignin. Examples of reactive compatibilizers include maleic anhydride modified PP (PP-MAH), maleic anhydride modified ethylene-butene copolymer (PE-MAH), ethylene-GMA copolymer (PE-GMA), maleic anhydride modified SEBS (SEBS-MAH), graft polymer PC-gP (GMA / AS), and oxazoline group-containing PS (PS-Ox). Among them, by using the maleic anhydride modified resin, the compatibility between the thermoplastic resin and the modified lignin becomes good, and a resin molded product having excellent mechanical properties, printability, coatability, and adhesion can be obtained. The acid value of the maleic anhydride modified resin is preferably 5 mgKOH / g or more and 50 mgKOH / g or less. When the acid value of the maleic anhydride modified resin is within the above range, compatibility and reactivity with the thermoplastic resin can be both achieved. The acid value can be evaluated according to JIS K 2510.
[0041] The content of the compatibilizer is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, and even more preferably 1% by mass or more and 5% by mass or less, based on the total mass (100% by mass) of the resin composition. When the content of the compatibilizer is equal to or more than the lower limit, the compatibility between the thermoplastic resin and the modified lignin is good, and a resin molded product having good coatability, printability, and adhesion is obtained. When the content of the compatibilizer is equal to or less than the upper limit, a resin molded product having good durability and mechanical properties is obtained.
[0042] The resin composition of the present embodiment may contain additives such as a filler, an antiblocking agent (AB agent), an antistatic agent, a plasticizer, a lubricant, an antioxidant, etc. These additives may be used alone or in combination of two or more kinds.
[0043] Since the resin composition of the present embodiment contains modified lignin with good processability and fluidity, it is possible to make lignin, which is a biomass material, compatible with general-purpose thermoplastic resins. Therefore, the resin composition of the present embodiment has excellent fluidity, is suitable for processing such as melt kneading, and has excellent dispersibility and compatibility with resins. Therefore, it is suitable for producing a resin molded product that has excellent durability and mechanical properties, as well as excellent coatability, printability, and adhesion.
[0044] <Method for producing resin composition> The method for producing a resin composition according to the present embodiment includes a step of kneading a thermoplastic resin and modified lignin modified with glycols to obtain a resin composition.
[0045] The method of kneading the thermoplastic resin and the modified lignin is not particularly limited, but examples thereof include a method of kneading the thermoplastic resin pellets while adding a dry solid material using a single-shaft kneader, a twin-shaft kneader, a multi-shaft kneader, a kneader, a roll mill, a planetary mixer, a twin-shaft mixer, or the like. The dry solid material and the thermoplastic resin may be kneaded using a combination of two or more types of devices. By performing the kneading process multiple times, it is possible to further improve the dispersibility of the modified lignin in the thermoplastic resin.
[0046] The temperature during the kneading process can be set appropriately within the range of temperatures at which the thermoplastic resin used can be melted, and is usually in the range of 100° C. to 300° C. The residence time during the kneading process is not particularly limited and can be set appropriately depending on the type of thermoplastic resin used, and is usually in the range of 0.5 minutes to 60 minutes. The kneading temperature is not particularly limited, but is preferably 160°C or higher and 300°C or lower. More preferably, it is 180°C or higher and 280°C or lower, and even more preferably, it is 200°C or higher and 260°C or lower. When the kneading temperature is above the lower limit, the flowability and processability of the thermoplastic resin and modified lignin are improved, and a resin molded product that is uniform and has good mechanical properties, coatability, and printability can be obtained. When the kneading temperature is below the upper limit, it is possible to suppress the deterioration of the thermoplastic resin and modified lignin due to heating, and a resin molded product that has good coatability, printability, and adhesion can be obtained. The kneading time is not particularly limited, but is preferably 0.5 minutes or more and 20 minutes or less, more preferably 1 minute or more and 10 minutes or less, and even more preferably 2 minutes or more and 5 minutes or less. When the kneading time is equal to or more than the lower limit, a uniform resin molded product in which the thermoplastic resin and the modified lignin are compatible with each other can be obtained. When the kneading time is equal to or less than the upper limit, the deterioration of the thermoplastic resin and the modified lignin can be suppressed.
[0047] The method for producing a resin composition according to the present embodiment is environmentally friendly and provides a resin composition that can provide a resin composition containing modified lignin in a simple procedure. The modified lignin is sufficiently dispersed and compatible in the obtained resin composition, so that a resin molded article can be obtained that fully exhibits the effects of lignin, such as improved strength properties, improved thermal dimensional stability, coatability, printability, and adhesion.
[0048] <Resin molded body> Hereinafter, a resin molded body according to one embodiment of the present invention will be described with reference to the drawings. FIG. 1 is a cross-sectional view that illustrates a resin molded body according to the present embodiment. The resin molded article of the present embodiment contains the resin composition of the above-described embodiment. As shown in FIG. 1, a resin molded product 1 of this embodiment is, for example, a film-like molded product.
[0049] The content of modified lignin in the resin composition 1 is, for example, preferably 3% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 80% by mass or less, and even more preferably 20% by mass or more and 70% by mass or less, relative to the total mass (100% by mass) of the resin composition 1. When the content of modified lignin is equal to or more than the lower limit, the degree of biomass conversion can be increased, and good mechanical properties and durability can be exhibited due to the antioxidant effect, flame retardancy, high heat resistance, high elastic modulus, etc. derived from the modified lignin. When the content of modified lignin is equal to or less than the upper limit, the flowability and processability during melt kneading are good.
[0050] The form of the resin molded body 1 is not particularly limited, and examples thereof include a film. In the case of a film, the thickness of the resin molded body 1 is determined taking into consideration the material and configuration, and is preferably, for example, 5 μm to 1000 μm, more preferably 10 μm to 700 μm, and even more preferably 50 μm to 500 μm. When the thickness of the resin molded body 1 is equal to or greater than the lower limit, the strength of the resin molded body 1 can be further increased. When the thickness of the resin molded body 1 is equal to or less than the upper limit, the flexibility of the resin molded body 1 is increased, making it easier to handle. The thickness of the resin molded body 1 can be measured, for example, with a thickness gauge or the like.
[0051] The resin molded body 1 may be a single-layer film made of a single resin, or a single-layer film or a film having two or more layers using a plurality of resins.
[0052] The antioxidant effect of the resin molded product 1 can be evaluated by immersing the resin molded product 1 in a hexane solution of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and measuring the change in absorbance at 509 nm due to DPPH in a radical state. The rate of change in absorbance is preferably 15% or more, more preferably 40% or more.
[0053] The flame retardancy of the resin molded body 1 can be evaluated by using a thermogravimetry and differential thermal analyzer to place about 10 mg of a sample in a platinum pan, raise the temperature from 25°C to 800°C at 10°C / min in a nitrogen atmosphere, and measure the remaining rate of the sample at 800°C using an empty aluminum pan as a reference. The remaining rate of the sample at 800°C is preferably 1% or more, and more preferably 10% or more.
[0054] The elastic modulus of the resin molded product 1 is not particularly limited, but is preferably 200 MPa or more, and more preferably 1200 MPa or more. The elastic modulus of the resin molded product 1 can be measured in accordance with JIS K 7127 by cutting the obtained film (resin molded product 1) into a dumbbell shape and subjecting it to a tensile test using a small benchtop tester.
[0055] The contact angle of the resin molded body 1 with water is preferably 40° or more and 105° or less, more preferably 50° or more and 90° or less. When the contact angle is equal to or more than the lower limit, a thermoplastic resin molded body 1 that combines durability and mechanical properties with printability, coatability, and adhesion can be obtained. When the contact angle is equal to or less than the upper limit, a resin molded body 1 that is excellent in processability, flowability, wettability, printability, and adhesion can be obtained. The contact angle of the resin molding 1 with water can be measured at 25°C using a contact angle meter (Kyowa Interface Science Co., Ltd., portable contact angle meter PCA-1) by dropping a 1.5 μL droplet of water onto the resin molding 1 and evaluating the contact angle of the droplet after 1 second.
[0056] The surface free energy of the resin molded body 1 is 30 mJ / m 2 More than 100mJ / m 2 It is preferable that the concentration is less than 60 mJ / m 2 More than 80mJ / m 2 When the surface free energy is within the above range, excellent durability, mechanical properties, printability, coatability, and adhesion can be achieved simultaneously. The surface free energy can be calculated by applying the contact angles of the resin molded body 1 measured in three types of solvents to the Kitazaki-Hata theory. The three types of solvents that can be used are water (distilled water), diiodomethane, and hexadecane. The value of the surface free energy can be calculated based on the arithmetic average value of the contact angles measured 10 times at different measurement points.
[0057] <Method for manufacturing resin molded body> The resin molded body of this embodiment may be a resin composition of the above embodiment molded into a film or the like by extrusion molding, or may be a master batch obtained by extruding the resin composition into a string shape, immersing it in cooling water, and cutting it with a cutter to re-pelletize it. The master batch in which the modified lignin is dispersed inside the thermoplastic resin is easy to handle, such as for transportation. Therefore, the master batch can be easily mixed with various other thermoplastic resins, and the modified lignin can be easily kneaded into various other thermoplastic resins.
[0058] The method for producing the resin molded product 1 of the present embodiment has a low environmental impact and can provide the resin composition 1 containing the modified lignin in a simple procedure. The modified lignin is sufficiently dispersed and compatible in the obtained molded product, so that the effects of lignin, such as improved strength properties, improved thermal dimensional stability, coatability, printability, and adhesion, can be fully exhibited.
[0059] <Laminated film> Hereinafter, a laminate film according to one embodiment of the present invention will be described with reference to the drawings. FIG. 2 is a cross-sectional view that illustrates a schematic view of the laminated film of the present embodiment. As shown in FIG. 2, a laminate film 3 of this embodiment includes, for example, a resin molded body 1 and a functional layer 2 formed on one main surface 1a of the resin molded body 1.
[0060] When forming the functional layer 2, for example, a coating liquid filtered using a filter is applied to one main surface 1a of the resin molding 1 by a wet coating method to form a coating film, and the coating film is then dried (to remove the solvent) to form the functional layer 2, which is a cured product of the resin composition. The coating liquid can be applied by a known wet coating method. Examples of the wet coating method include roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating.
[0061] The coating film can be dried by known methods such as hot air drying, hot roll drying, infrared irradiation, etc. The coating film can be dried at a temperature of, for example, 50° C. to 200° C. The drying time varies depending on the coating film thickness, drying temperature, etc., but can be, for example, 1 second to 5 minutes.
[0062] Examples of functional materials contained in the functional layer 2 include UV absorbers, plasticizers, antioxidants, lubricants, design materials, antifungal agents, preservatives, antifogging agents, antibacterial agents, antiviral agents, moisturizers, adsorbents, etc.
[0063] In the resin molded body 1, one main surface 1a on which the functional layer 2 is formed may be subjected to a surface treatment such as a chemical treatment, a solvent treatment, a corona treatment, a low-temperature plasma treatment, an ozone treatment, etc. This can further increase the adhesion between the one main surface 1a of the resin molded body 1 and the functional layer 2.
[0064] <Lamination film> A lamination film according to one embodiment of the present invention is a film including the resin molded article 1 of the above-described embodiment and a laminate layer formed on one or both main surfaces of the resin molded article 1. The laminate layer may be, for example, a sealant material such as a PP film or a polyethylene (PE) film. These sealant materials melt when heated, so that a package, which will be described later, can be easily obtained by overlapping the laminate layers and heating them (heat sealing).
[0065] The thickness of the laminate layer is, for example, preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 50 μm or less, and even more preferably 3 μm or more and 30 μm or less. When the thickness of the laminate layer is equal to or more than the lower limit, the sealing property of the resulting package can be further improved. When the thickness of the laminate layer is equal to or less than the upper limit, the flexibility of the lamination film is further improved, making it easier to handle. The thickness of the laminate layer can be determined, for example, by observing a cross section of the lamination film cut in the thickness direction with a microscope or the like.
[0066] The method for forming the laminate layer is not particularly limited, and examples include a method of applying an adhesive to one or both surfaces of the resin molded body 1 and then laminating a sealant material, a method of overlapping a sealant material on one or both main surfaces of the resin molded body 1 and heating it while pressing it, and a method of co-extruding the resin molded body 1 and the sealant material. A preferred method for forming the laminate layer is to apply an adhesive to one or both main surfaces of the resin molded body 1 and then attach a sealant material thereto, since this can increase the physical strength of the lamination film.
[0067] The adhesive used for forming the laminate layer is not particularly limited, and examples thereof include two-liquid curing type ester adhesives, ether adhesives, urethane adhesives, and epoxy adhesives.
[0068] The heating temperature when heating to form the laminate layer is, for example, preferably 40° C. or higher, more preferably 50° C. or higher, and even more preferably 60° C. or higher. When the heating temperature when heating to form the laminate layer is equal to or higher than the lower limit, the adhesion between the resin molded body 1 and the laminate layer can be further improved. The upper limit of the heating temperature when heating to form the laminate layer is, for example, 250° C. or lower, from the viewpoint of preventing each layer constituting the lamination film from being damaged by heat.
[0069] When a laminate layer is formed on one of the main surfaces 1a of the resin molded body 1, the laminate layer is formed on the surface of either the resin molded body 1 or the functional layer 2. When a laminate layer is formed on the surface of the resin molded body 1, the functional layer 2 is located on the outermost layer of the package made by bagging the lamination film, and the effect of the resin molded body 1 improves adhesion, and the functional layer 2 can protect the resin molded body 1 and the laminate layer. In addition, when a laminate layer is formed on the surface of the functional layer 2, the resin molded body 1 is located on the outermost layer of the package made by bagging the lamination film, and the resin molded body 1 can suppress deterioration of the laminate layer due to oxygen and ultraviolet rays, and can suppress damage to the functional layer 2.
[0070] The lamination film of this embodiment uses the resin molded body 1 having the functional layer 2, and therefore can effectively utilize biomass raw materials. The lamination film of the present embodiment uses the resin molded body 1, and therefore has the same functionalities as the laminated film, such as oxidation resistance, ultraviolet absorbing ability, flame retardancy, and high elastic modulus. The lamination film of the present embodiment has an antioxidant property, and therefore can suppress its own oxidative deterioration and can suppress peeling between layers, thereby improving the adhesion between layers and providing excellent impact resistance.
[0071] ≪Packaging body≫ The package according to one embodiment of the present invention is produced by forming a bag from the resin molded body 1 and the laminated film 3. Examples of the packaging body include a resin molded body 1 and a bag made by applying an adhesive to the surface of the functional layer 2 of the laminated film 3 and laminating a sealant material to obtain a lamination film, and then heat-sealing the sealant materials of the obtained lamination film.
[0072] The adhesive may be a known hot melt adhesive, a reactive hot melt adhesive, etc. More specifically, examples of the adhesive include a two-liquid curing type ester adhesive, an ether adhesive, a urethane adhesive, an epoxy adhesive, etc. Examples of the sealant material include a PP film and a polyethylene (PE) film.
[0073] Examples of the form of the package include a palm-sealed bag, a three-side sealed bag, a four-side sealed bag, a gusseted bag, a stand-up bag, and bags with zippers attached to these bags. Further, for example, the packaging body may be a container having a container body with an opening and a lid body made of a laminated film 3, in which a sealant material is applied to the periphery of the opening of the container body and the laminated film 3 is heat-sealed to the container body.
[0074] The package of the present embodiment is a bag made from the resin molded body 1 containing modified lignin and the laminated film 3, and therefore allows for effective use of biomass raw materials. The packaging body of this embodiment is a bag made from the resin molding 1 or the laminated film 3, and therefore has the same functionality as the laminated film 3, such as antioxidant properties, ultraviolet absorption ability, mechanical properties, coatability, printability, and adhesion. The packaging material of the present embodiment has an antioxidant property, and therefore can suppress its own oxidative deterioration and can suppress peeling between layers, thereby improving the adhesion between the layers and providing excellent impact resistance. EXAMPLES
[0075] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the following examples, unless otherwise specified, "%" indicates % by mass (w / w%) and "parts" indicates parts by mass.
[0076] <Resin> thermoplastic resin Polypropylene (PP): Prime Polypro E-2000GV (Prime Polymer) Polyethylene (PE): Evolu SP3530 (Prime Polymer) Thermoplastic polyurethane (TPU): Elastollan ET385 (manufactured by Mitsui DuPont Polychemicals) Ethylene and methacrylic acid copolymer resin (EMAA): Nucrel AN4228C (manufactured by BASF Japan) 6-Nylon (PA6): UBE NYLON 1022B (manufactured by Ube Industries) thermosetting resin Phenolic resin (PF): Novolac type phenolic resin (manufactured by Asahi Yukizai Kogyo Co., Ltd.)
[0077] <Melt viscosity measurement of thermoplastic resin> The melt viscosity of each thermoplastic resin was measured using a rheometer. The melt viscosity at 100 rad / s was measured using parallel plates with a diameter of 25 mm under a nitrogen atmosphere at a temperature of 230°C and at frequencies from 100 rad / s to 1 rad / s. From the measured melt viscosity values, the melt viscosity of the thermoplastic resin of each example was evaluated on a three-level scale of "◎", "◯", and "×" based on the following evaluation criteria. When the melt viscosity of the thermoplastic resin is evaluated as "◎" or "◯", the modified lignin is easily dispersed and compatible, and a resin molded product with excellent mechanical properties, coatability, printability, and lamination properties can be obtained. The results are shown in Table 1. Evaluation Criteria ◎: Melt viscosity is 100 Pa·s or more and 5000 Pa·s or less. Good: Melt viscosity is 10 Pa·s or more but less than 100 Pa·s, or more than 5000 Pa·s but less than 10000 Pa·s. ×: Melt viscosity is less than 10° or more than 10,000°, or cannot be measured.
[0078] <Contact angle measurement of thermoplastic resin> The thermoplastic resin pellets of each example were heated to 230°C, compression molded, and cooled to produce a thermoplastic resin sheet as a resin molded body. Water (distilled water) was dropped onto the thermoplastic resin sheet, and the contact angle of water was measured by the liquid drop method using a contact angle meter (Kyowa Interface Science Co., Ltd., portable contact angle meter PCA-1). The temperature and humidity during the measurement were 23°C and 50% RH, respectively, the amount of liquid was 1.5 μL, and the contact angle was obtained 1 second after the liquid landed. The contact angle was measured 10 times by changing the measurement location, and the arithmetic average value was taken. From the measured water contact angle value, the contact angle of the thermoplastic resin of each example was evaluated in three stages of "◎", "〇", and "×" based on the following evaluation criteria. If the contact angle of the thermoplastic resin is evaluated as "◎" or "〇", the compatibility with the modified lignin is good, and a resin molded body with excellent mechanical properties, coatability, printability, and adhesion can be obtained. The results are shown in Table 1. Evaluation Criteria ◎: Water contact angle is between 80° and 100°. Good: The water contact angle is 30° or more and less than 80°, or more than 100° and less than 120°. ×: The contact angle of water is less than 30° or more than 120°.
[0079] <Surface free energy measurement of thermoplastic resin> For each resin molded body prepared above, the contact angles measured with three types of solvents were applied to the Kitazaki-Hata theory to calculate the surface free energy. The three solvents used were water (distilled water), diiodomethane, and hexadecane, and the contact angle measurement conditions were the same as those in the above-mentioned "Contact angle evaluation". The surface free energy value was calculated based on the arithmetic average value of the contact angle measured 10 times at different measurement points. The surface free energy was evaluated in three stages, "◎", "〇", and "×", based on the following evaluation criteria. If the surface free energy is evaluated as "◎" or "〇", the wettability is good, the occurrence of bleeding and repelling can be suppressed, and a resin molded body with excellent printability and adhesion can be obtained. The results are shown in Table 1. Evaluation Criteria ◎: Surface free energy value is 50mJ / m 2 More than 80mJ / m 2 below. ○: Surface free energy value is 30mJ / m 2 More than 50mJ / m 2 Less than or equal to 80 mJ / m 2 Super 100mJ / m 2 The end. ×: Surface free energy value is 30 mJ / m 2 Less than or equal to 100 mJ / m 2 Super.
[0080] <<Calculation of SP value of thermoplastic resin>> Using the Hansen Solubility Parameter software HSPiP (Hansen Solubility Parameter in Practice), the SP value of the constituent monomers was calculated from the molecular structure of the thermoplastic resin composition. The chemical structure was entered in Smile notation on the input screen of the software, and the HSP value was calculated using the Yamamoto Molecular Break (Y-MB) method, and the SP value was obtained from the total value of the dispersion term, polarity term, and hydrogen bond term. From the measured mass average molecular weight, the SP value of each thermoplastic resin was evaluated on a three-level scale of "◎", "◯", and "×" based on the following evaluation criteria. When the SP value is evaluated as "◎" or "◯", the compatibility with the modified lignin is good, and a resin molded product with excellent mechanical properties, coatability, printability, and lamination properties can be obtained. The results are shown in Table 1. Evaluation Criteria ◎: SP value is between 20 and 30. ○: SP value is between 10 and 20, or between 30 and 40. ×: SP value is less than 10 or more than 40.
[0081] Table 1 shows the evaluation results for each thermoplastic resin.
[0082] [Table 1]
[0083] <Lignin> <Production Example 1> <Modified lignin 1: PEG400 modified lignin> A lignin modified with polyethylene glycol having a number average molecular weight of 400 was produced. 230 parts by mass of polyethylene glycol (PEG400) having a number average molecular weight of 400 and 0.69 parts by mass of sulfuric acid as an acid catalyst (0.3 parts by mass relative to 100 parts by mass of PEG400) were placed in a reaction vessel and stirred. Next, 46 parts by mass of bone-dried cedar wood flour was added to the reaction vessel, and the temperature was raised to 140° C. under normal pressure, and the mixture was reacted for 90 minutes with stirring. Next, the reaction vessel was cooled, and after confirming that the temperature was 40°C or less, 280 parts by mass of sodium hydroxide (0.2 mol / L) was added and stirred for 30 minutes. The obtained solid component (pulp) was removed by a filter press, and the solution component was recovered. Sulfuric acid was added to the obtained solution component to adjust the pH to 2.0. This resulted in a suspension of modified lignin, which was then recovered by centrifugation.
[0084] <Modified lignin 2: PEG200 modified lignin> A modified lignin was obtained in the same manner as in Production Example 1, except that polyethylene glycol having a number average molecular weight of 200 was used instead of polyethylene glycol having a number average molecular weight of 400.
[0085] <Modified lignin 3: PEG1000 modified lignin> A modified lignin was obtained in the same manner as in Production Example 1, except that polyethylene glycol having a number average molecular weight of 1,000 was used instead of the polyethylene glycol having a number average molecular weight of 400.
[0086] <Modified lignin 4: PEG2000 modified lignin> A modified lignin was obtained in the same manner as in Production Example 1, except that polyethylene glycol having a number average molecular weight of 2,000 was used instead of the polyethylene glycol having a number average molecular weight of 800.
[0087] <Acetic acid modified lignin> 100 parts by mass of corn stover was mixed with 1000 parts by mass of 95% acetic acid and 3 parts by mass of sulfuric acid, and reacted under reflux for 4 hours. After the reaction, the mixture was filtered to remove the pulp, and the pulp waste liquid was collected. Next, the acetic acid in the pulp waste liquid was removed using a rotary evaporator and concentrated to 1 / 10 of its volume. After that, 10 times the amount (by mass) of water as the concentrated liquid was added and filtered to obtain acetic acid-modified lignin as a solid.
[0088] <Lignosulfonic acid> Sodium lignosulfonate, Sanex (registered trademark) P252 (mass average molecular weight: more than 1000 and less than 5000), manufactured by Nippon Paper Industries Co., Ltd.
[0089] <Alkaline lignin> Alkaline lignin, L0082 (mass average molecular weight: over 10,000 and up to 20,000), manufactured by Tokyo Chemical Industry Co., Ltd.
[0090] <Measurement of mass average molecular weight of modified lignin> The mass average molecular weights of modified lignins 1 to 4, acetic acid modified lignin, lignosulfonic acid, and alkaline lignin in this example were measured by GPC using the following measuring device under the following measuring conditions. <Measurement equipment> GPC equipment: HLC-8320GPC EcoSEC, manufactured by Tosoh Corporation. Columns used: TSKgelguardcolumn SuperMP(HZ)-M, TSKgel SuperMultipore HZ-M, TSKgel SuperH-RC. Detector: RI detector, manufactured by Tosoh Corporation. <Measurement conditions, etc.> ·Eluent: THF. ·Eluent flow rate: 0.35mL / min. Column temperature: 40°C. -Measurement sample concentration: 0.2% by mass. Standard material: Standard polystyrene PStQuickMP-M (Tosoh Corporation). Calibration curve: polystyrene standards. From the measured mass average molecular weight, the mass average molecular weight of each modified lignin was evaluated on a three-level scale of "◎", "◯", and "×" based on the following evaluation criteria. When the modified lignin is evaluated as "◎" or "◯", it is possible to obtain a resin molded product having excellent flowability and processability in melt kneading and excellent mechanical properties. The results are shown in Table 2. Evaluation Criteria ◎: Mass average molecular weight is 5,000 or more and 20,000 or less. Good: Mass average molecular weight is 100 or more and less than 5,000, or more than 20,000 and less than 50,000. ×: Mass average molecular weight is less than 100 or more than 50,000.
[0091] <Melt viscosity measurement of lignin> The melt viscosity of each lignin was measured using a rheometer. The melt viscosity at 100 rad / s was measured at frequencies from 100 rad / s to 1 rad / s at a temperature of 230°C under a nitrogen atmosphere using parallel plates with a diameter of 25 mm. From the measured melt viscosity values, the melt viscosity of each modified lignin was evaluated on a three-level scale of "◎", "◯", and "×" based on the following evaluation criteria. When the melt viscosity of the lignin is evaluated as "◎" or "◯", it is possible to obtain a resin molded product having excellent flowability and processability in melt kneading and excellent mechanical properties. The results are shown in Table 2. Evaluation Criteria ◎: Melt viscosity is 100 Pa·s or more and 20,000 Pa·s or less. Good: Melt viscosity is 10 Pa·s or more but less than 100 Pa·s, or more than 20,000 Pa·s but less than 50,000°. ×: Melt viscosity is less than 10 Pa·s, or exceeds 50,000 Pa·s, or cannot be measured.
[0092] <Contact angle measurement of lignin> The lignin of each example was dissolved in a solvent such as THF at a concentration of 10% by mass, coated on a PET substrate, and dried at 100°C for 1 minute to prepare a modified lignin coating film with a thickness of approximately 2 μm. Water (distilled water) was dropped onto the surface of the modified lignin coating film, and the contact angle of water was measured by the liquid drop method using a contact angle meter (Kyowa Interface Science Co., Ltd., portable contact angle meter PCA-1). The temperature and humidity at the time of measurement were 23°C and 50% RH, respectively, the amount of liquid was 1.5 μL, and the contact angle was obtained 1 second after the liquid was applied. The contact angle was measured 10 times at different measurement points, and the arithmetic average value was taken. Based on the measured water contact angle value, the contact angle of the modified lignin of each example was evaluated on a three-level scale of "◎", "〇", and "×" based on the following evaluation criteria. When the modified lignin contact angle is evaluated as "◎" or "◯", the wettability is good, the occurrence of bleeding and repelling can be suppressed, and a resin molded product with excellent printability and adhesion can be obtained. The results are shown in Table 2. Evaluation Criteria ◎: Water contact angle is between 60° and 80°. ○: The water contact angle is 30° or more and less than 60°, or more than 80° and less than 100°. ×: The contact angle of water is less than 30° or more than 100°.
[0093] <Surface free energy measurement of modified lignin> For each coating film prepared above, the contact angles measured with three types of solvents were applied to the Kitazaki-Hata theory to calculate the surface free energy. The three solvents used were water (distilled water), diiodomethane, and hexadecane, and the contact angle measurement conditions were the same as those in the above <Contact angle measurement of lignin>. The surface free energy value was calculated based on the arithmetic average value of the contact angles measured 10 times at different measurement points. The surface free energy was evaluated on a three-level scale of "◎", "〇", and "×" based on the following evaluation criteria. If the surface free energy is evaluated as "◎" or "〇", the wettability is good, bleeding and cissing can be suppressed, and a resin molded product with excellent printability and adhesion can be obtained. The results are shown in Table 2. Evaluation Criteria ◎: Surface free energy value is 60mJ / m 2 More than 80mJ / m 2 below. ○: Surface free energy value is 40mJ / m 2 More than 60mJ / m 2 Less than or equal to 80 mJ / m 2 Super 120mJ / m 2 below. ×: Surface free energy value is 40 mJ / m 2 Less than or equal to 120 mJ / m 2 Super.
[0094] Table 2 shows the evaluation results of the lignin in each example.
[0095] [Table 2]
[0096] [Example 1] <Preparation of resin composition> 90 parts by mass of PP as thermoplastic resin pellets and 10 parts by mass of modified lignin 1 (PEG400 modified lignin) as modified lignin were mixed and kneaded using a twin-screw kneader (Labo Plastomill, manufactured by Toyo Seiki Seisakusho). The kneading temperature was 230°C, and the screw rotation speed during kneading was 10 rpm. The obtained resin composition was extruded into a string shape, immersed in cooling water, and further cut with a cutter to be re-pelletized. A resin composition containing modified lignin was obtained by the above process.
[0097] <Production of resin molded body> The pellets of the resin composition prepared in the previous section were used as a master batch, and an extruded film was produced. The same Labo Plastomill as in the previous section was used to form the extruded film, and the resin discharged from the Labo Plastomill was taken up using a film take-up machine, which is a utility dedicated to the Labo Plastomill, to produce a resin molded body as a film with a thickness of about 250 μm. The kneading temperature was 230°C, and the screw rotation speed during kneading was 20 rpm.
[0098] [Example 2] In Example 1, 95 parts by mass of PP and 5 parts by mass of modified lignin 1 were mixed to prepare a resin composition and a resin molded product.
[0099] [Example 3] In Example 1, 70 parts by mass of PP and 30 parts by mass of modified lignin 1 were mixed to prepare a resin composition and a resin molded product.
[0100] [Example 4] In Example 1, 50 parts by mass of PP and 50 parts by mass of modified lignin 1 were mixed to prepare a resin composition and a resin molded product.
[0101] [Example 5] In Example 1, 88 parts by mass of PP, 2 parts by mass of maleic acid-modified PP Rike-Aid MG-441P (manufactured by Riken Vitamin Co., Ltd.) as a compatibilizer, and 10 parts by mass of modified lignin were mixed to produce a resin composition and a resin molded body.
[0102] [Example 6] In Example 1, a resin composition and a resin molded product were produced using PE instead of PP as the thermoplastic resin.
[0103] [Example 7] In Example 1, a resin composition and a resin molded article were produced using TPU instead of PP as the thermoplastic resin.
[0104] [Example 8] In Example 1, a resin composition and a resin molded product were produced using EMAA as the thermoplastic resin instead of PP.
[0105] [Example 9] In Example 1, a resin composition and a resin molded body were produced using PA6 as the thermoplastic resin pellets.
[0106] [Example 10] In Example 1, modified lignin 2 (PEG200-modified lignin) was used instead of modified lignin 1 (PEG400-modified lignin) as the modified lignin, to prepare a resin composition and a resin molded product.
[0107] [Example 11] In Example 1, modified lignin 3 (PEG1000-modified lignin) was used instead of modified lignin 1 (PEG400-modified lignin) as the modified lignin, to prepare a resin composition and a resin molded product.
[0108] [Example 12] In Example 1, a resin composition and a resin molded product were produced using PEG2000-modified lignin instead of modified lignin 1 (PEG400-modified lignin) as the modified lignin.
[0109] [Comparative Example 1] In Example 1, a resin composition and a resin molded product were produced using acetic acid modified lignin instead of modified lignin 1 (PEG400 modified lignin) as the modified lignin.
[0110] [Comparative Example 2] In Example 1, a resin composition and a resin molded product were produced using sodium lignin sulfonate (Sunex P252) instead of modified lignin 1 (PEG400 modified lignin) as the modified lignin.
[0111] [Comparative Example 3] In Example 1, a resin composition and a resin molded product were produced using alkaline lignin (L0082) instead of modified lignin 1 (PEG400-modified lignin) as the modified lignin.
[0112] [Comparative Example 4] In Example 2, an attempt was made to produce a resin composition and a resin molded body by using PF as a thermosetting resin instead of PP, which is a thermoplastic resin, and blending hexamethylenetetramine (manufactured by Lignite Corporation) as a curing agent; however, the pellets of the resin composition did not melt, and a resin molded body could not be produced.
[0113] Table 3 shows the compositions of the resin molded bodies in Examples 1 to 12 and Comparative Examples 1 to 4.
[0114] [Table 3]
[0115] <Evaluation of antioxidant properties> The resin molded bodies prepared above were each cut into a size of 1 cm x 1.5 cm to be used as samples. Each sample was immersed in 6 mL of a hexane solution of 2,2-diphenyl-1-picrylhydrazyl (DPPH) with a concentration of 25 mg / L and placed in a thermostatic bath at 25°C (hereinafter referred to as "DPPH-containing hexane solution"). Each sample was also immersed in 5 mL of hexane and placed in a thermostatic bath at 25°C (hereinafter referred to as "DPPH-free hexane solution"). The absorbance A0 of the hexane solution of DPPH with a concentration of 25 mg / L before the sample was immersed, the absorbance A1 of the hexane solution containing DPPH after 24 hours of immersion, and the absorbance A2 of the hexane solution not containing DPPH after 24 hours of immersion were measured using an ultraviolet-visible spectrophotometer (Hitachi, U-4100), and the absorbance change rate (A0-(A1-A2)) / A0×100[%] was calculated. The absorbance of each solution was measured at 509 nm. The antioxidant properties of the resin molded bodies of each example were evaluated on a three-level scale, "◎", "〇", and "×", based on the following evaluation criteria. The results are shown in Table 4. Evaluation Criteria ◎: The absorbance change rate is 40% or more. ○: The absorbance change rate is 15% or more and less than 40%. ×: The rate of change in absorbance is less than 15%.
[0116] <Evaluation of survival rate at 800℃> The residual rate at 800°C was evaluated using a thermogravimetry and differential thermal analyzer (STA7200RV, Hitachi High-Tech Science Corporation). Approximately 10 mg of sample was added to a platinum pan, and the temperature was raised from 25°C to 800°C at 10°C / min. in a nitrogen atmosphere. The residual rate of the sample at 800°C was measured using an empty aluminum pan as a reference. The results are shown in Table 4. Evaluation Criteria ◎: Residual rate is 10% or more. ○: Residual rate is between 1% and 10%. ×: Residual rate is less than 1%.
[0117] <Evaluation of mechanical properties> The obtained film (resin molded product) was cut into a dumbbell shape and the tensile strength was measured using a small tabletop tester EZ-LX (manufactured by Shimadzu Corporation) according to JIS K 7127. The measurement conditions were as follows. The results are shown in Table 4. <Measurement conditions> Sample piece: Dumbbell piece (test piece 5). Load cell: 1kN. Pulling speed: 50mm / min. ·Distance between gauge lines: 80mm. N:5. The strain (%) and stress (MPa) at the upper yield point, which is the maximum strength of the strength-elongation curve obtained in the tensile strength measurement, the elongation (%) and stress (MPa) at break, and the average value of the elastic modulus (MPa) were recorded. The results are shown in Table 4. In the table, "-" indicates that the tensile strength was not measured. From the measured elastic modulus value, the elastic modulus of the resin molded article of each example was evaluated into three levels of "◎", "◯", and "×" based on the following evaluation criteria. The results are shown in Table 4. Evaluation Criteria ◎: 1200MPa or more. ○: Elastic modulus is 200MPa or more and less than 1200MPa. ×: Elastic modulus is less than 200 MPa.
[0118] <Contact angle evaluation> Water (distilled water) was dropped onto the surface of each resin molded body prepared above, and the contact angle of water was measured by the drop method using a contact angle meter (Kyowa Interface Science Co., Ltd., portable contact angle meter PCA-1). The temperature and humidity during the measurement were 23°C and 50% RH, respectively, the amount of liquid was 1.5 μL, and the contact angle was obtained 1 second after the liquid landed. The contact angle was measured 10 times at different measurement points, and the arithmetic average value was taken as the average value. From the measured water contact angle value, the contact angle of each resin molded body was evaluated on a three-level scale of "◎", "〇", and "×" based on the following evaluation criteria. If the contact angle is evaluated as "◎" or "〇", the wettability between the resin molded body and the liquid droplet is good, the occurrence of bleeding and repelling can be suppressed, and the printability and adhesion are excellent. The results are shown in Table 4. Evaluation Criteria A: The water contact angle is between 50° and 90°. B: The contact angle of water is 40° or more and less than 50°, or more than 90° and less than 105°. C: The contact angle of water is less than 40° or more than 105°.
[0119] <Evaluation of surface free energy> For each resin molded body prepared above, the contact angles measured with three types of solvents were applied to the Kitazaki-Hata theory to calculate the surface free energy. The three solvents used were water (distilled water), diiodomethane, and hexadecane, and the contact angle measurement conditions were the same as those in the above-mentioned <Contact angle evaluation>. The surface free energy value was calculated based on the arithmetic average value of the contact angle measured 10 times at different measurement points. The surface free energy was evaluated in three stages, "◎", "〇", and "×", based on the following evaluation criteria. If the surface free energy is evaluated as "◎" or "〇", the wettability between the functional layer and the droplets is good, the occurrence of bleeding and repelling can be suppressed, and the printability and adhesion are excellent. The results are shown in Table 4. Evaluation Criteria ◎: Surface free energy value is 60mJ / m 2 More than 80mJ / m 2 below. ○: Surface free energy value is 30mJ / m 2 More than 60mJ / m 2 Less than or equal to 80 mJ / m 2 Super 100mJ / m 2 below. ×: Surface free energy value is 30 mJ / m 2 Less than or equal to 100 mJ / m 2 Super.
[0120] <Evaluation of printability> For each of the resin molded articles produced above, the printability was evaluated according to the following procedure. A water-based gravure ink (Hydric (registered trademark) PRP-500, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) was used as the printing ink and printed on the surface of the resin molded body, and an area of 5 cm x 5 cm was observed by image analysis. Based on the following evaluation criteria, the printability of the laminated film of each example was evaluated on a three-level scale of "◎", "◯", and "×". In the following evaluation criteria, "%" represents the percentage of the area where bleeding or repelling could be confirmed. The results are shown in Table 4. Evaluation Criteria ⊚: Bleeding and repelling are less than 10%. ○: Bleeding or repelling is 10% or more but less than 30%. ×: Bleeding or repelling is 30% or more.
[0121] <Evaluation of Coatability> PVA was dissolved in water (distilled water) as a water-based resin to prepare a 10% aqueous solution of PVA. The coating solution was filtered through a filter with a pore size of 5.0 μm, and the coating solution was applied to one side of the resin molded body in each example with a wire bar and dried at 100° C. to form a functional layer with a thickness of 10 μm, thereby producing a laminated film. A 5cm x 5cm area was observed by image analysis. Based on the following evaluation criteria, the printability of the laminated film of each example was evaluated on a three-level scale of "◎", "◯", and "×". In the following evaluation criteria, "%" indicates the percentage of the area where bleeding or repelling could be confirmed. The results are shown in Table 4. Evaluation Criteria ⊚: Bleeding and repelling are less than 10%. ○: Bleeding or repelling is 10% or more but less than 30%. ×: Bleeding or repelling is 30% or more.
[0122] <Evaluation of adhesion> The resin molded article of each example was evaluated for adhesion according to the following procedure. A 60 μm thick unstretched polypropylene film (CPP, product name "Treyfan (registered trademark) ZK207", manufactured by Toray Film Processing Co., Ltd.) was attached to both sides of the resin molded body of each example using a two-liquid adhesive (product name "A-525 / A-52", manufactured by Mitsui Chemicals, Inc.) to prepare a laminate film. This laminate film was cut into a size of 10 cm x 10 cm and subjected to high-temperature and high-pressure steam treatment at 121 ° C. for 20 minutes in an autoclave. The laminate strength of the laminate film after the treatment was measured in accordance with "7.2 Tensile force and tensile elongation at break test" described in JIS Z1707:2019. Specifically, the laminate film was first cut into a strip of 15 mm width. Next, the test sample cut into a strip was peeled from the CPP film at a peeling speed of 300 mm / min using a tensile tester (product name "Tensilon (registered trademark) RTC-1250", manufactured by Orientec Co., Ltd.) so that the resin molded body and the CPP film faced each other (i.e., the peeling angle was T-shaped), and the strength required for peeling (unit: N / 15 mm) was measured as the laminate strength. The adhesion of the resin molded body of each example was evaluated into three levels, A to C, based on the following evaluation criteria. The results are shown in Table 4. Evaluation Criteria ◎: Lamination strength is 2N / 15mm or more. Good: Laminate strength is 1.5N / 15mm or more and less than 2N / 15mm. ×: Lamination strength is less than 1.5N / 15mm.
[0123] Table 4 shows the evaluation results of Examples 1 to 12 and Comparative Examples 1 to 3.
[0124] [Table 4]
[0125] As shown in Table 4, Examples 1 to 12 in which modified lignin was applied to various general-purpose thermoplastic resins showed high elastic modulus, flame retardancy, and antioxidant effect, and were confirmed to have excellent mechanical properties and durability, as well as printability, coatability, and adhesion. By using modified lignin modified with glycols, it is possible to obtain a uniform resin molded body with excellent fluidity and processability and good compatibility with various general-purpose thermoplastic resins. For this reason, it is considered that mechanical properties and durability, as well as printability, coatability, and adhesion, were all achieved. The antioxidant property tended to be higher as the content of modified lignin was higher, and the adhesion property tended to be higher as the antioxidant property was higher. In contrast, in Comparative Examples 1 to 3, which used lignin that was not modified with glycols, mechanical properties and durability could not be achieved in combination with printability, coatability, and adhesion. This is believed to be because the lignins in Comparative Examples 1 to 3 had poor fluidity during processing and poor compatibility with thermoplastic resins. In Comparative Example 4, the resin was cured by heating, making it impossible to process, and therefore a resin molded article could not be produced. [Industrial Applicability]
[0126] According to the present invention, it is possible to disperse and solubilize biomass materials in general-purpose thermoplastic resins without reducing processability, and the addition of biomass materials improves the mechanical properties and durability of thermoplastic resin molded articles, and also provides resin molded articles with excellent printability. These resin molded articles can be used for building materials, packaging materials, electronic components, etc. [Explanation of symbols]
[0127] 1 Resin molding 2. Functional Layer 3. Laminated Film
Claims
1. A resin composition comprising a thermoplastic resin and a modified lignin modified with glycols.
2. The surface free energy of a resin molded body made of the thermoplastic resin and the modified lignin is 30 mJ / m 2 100mJ / m or more 2 The resin composition according to claim 1, wherein:
3. The resin composition according to claim 1 , wherein the SP value of the monomer constituting the thermoplastic resin is 10 or more and 40 or less.
4. A resin molded body made of the thermoplastic resin and the modified lignin has a contact angle with water of 30° or more and 120° or less, The surface free energy of a resin molded body made of the thermoplastic resin and the modified lignin is 40 mJ / m 2 90mJ / m or more 2 The resin composition according to claim 1, wherein:
5. The resin composition according to claim 1, wherein the thermoplastic resin has a melt viscosity at 230°C and 100 rad / s of 10 Pa·s or more and 10,000 Pa·s or less.
6. The resin composition according to claim 1, wherein the modified lignin has a mass average molecular weight of 100 or more and 50,000 or less.
7. The contact angle of the coating film made of the modified lignin with water is 30° or more and 100° or less, The surface free energy of the coating film made of the modified lignin is 40 mJ / m 2 120mJ / m or more 2 The resin composition according to claim 1, wherein:
8. The resin composition according to claim 1, wherein the modified lignin has a melt viscosity at 230°C and 100 rad / s of 10 Pa·s or more and 50,000 Pa·s or less.
9. The resin composition according to claim 1, wherein the glycols include at least one selected from the group consisting of polyethylene glycol, methoxypolyethylene glycol, polypropylene glycol, polybutylene glycol, and polyoxyalkylene bisphenol.
10. The resin composition of claim 1 , further comprising a compatibilizer.
11. A resin molded product comprising the resin composition according to any one of claims 1 to 10.
12. A method for producing the resin composition according to any one of claims 1 to 10, A method for producing a resin composition, comprising a step of kneading a thermoplastic resin and a modified lignin modified with glycols to obtain a resin composition.
Citation Information
Patent Citations
Device for manufacturing double bag
JP1982087354A
Resin composition
JP2021123717A
Powder composition and use of same
WO2021015190A1
